Analisis Putusan Pengadilan Agama Kandangan Nomor 51/PDT.G/2021/PA.KDG Tentang Isbat Nikah Poligami Perspektif Sema Nomor 3 Tahun 2018 dan Maqasid Syari’ah - Lela Tari; Iwan Nasution (UNES Law Review, 2023)
The reseach aims to find out how the basis for the judge's consideration in deciding the polygamous marriage isbat determination case No. 51/Pdt.G/2021/PA.Kdg, where the decision is not in accordance with SEMA Number 3/2018 which states that "Isbat polygamous marriage based on irri marriage, even though it is intended to fulfill the interests of children, must be declared unacceptable. Meanwhile, related to children, it can be submitted through an application for the origin of the child ". The type of research is research with a normative juridical approach using legislation and literature. The primary data source of this research is the Religious Court Decision 51/Pdt.G/2021/PA.Kdg. The results of this study indicate that there are still judges who do not implement Supreme Court Circular Letter Number 3 of 2018 which clearly prohibits polygamous marriage isbat for any reason. However, when viewed in the realm of Maqashid Shari'ah, polygamous marriage isbat is not a forbidden thing because it contains several benefits and will give birth to many disadvantages if it is not allowed.